A virtual indoor environment model—a useful tool for design - Niemelä, Raimo; Hongisto, Valtteri; Koskela, Hannu; Sandberg, Esa (SJWEH Supplements, 2008)
' ' OBJECTIVES ': 'The aim of this paper is to present an integrated approach, in terms of a virtual room model, for visualizing the model predictions of various indoor environment parameters in order to enhance interaction between the members of the design team and the occupants. ' ' METHODS ': 'The approach is based on room model and virtual room model concepts. The room model is a database containing structured information on geometry, the surface material of a room, product model data, operation conditions, and target levels for different indoor parameters. The virtual room model is a three-dimensional presentation of the room under consideration. From the room model the relevant geometric and boundary condition data are migrated to application models that calculate the specific indoor-environment parameters, which are then visualized in the virtual room model. ' ' RESULTS ': 'The basic idea of the approach is that, although different application software are used in the calculations, they use the same input data, and the simulation results are shown in the same virtual environment. ' ' CONCLUSIONS ': 'By enhancing collaboration and integration in the design phase, the approach should reduce the design cycle and make the design and construction phases more accurate.
Keywords: acoustics; air quality; airflow pattern; design; design method; indoor environment; indoor environment model; thermal conditions; virtual indoor environment model; virtual model; visualization